2007
DOI: 10.1103/physrevb.75.165313
|View full text |Cite
|
Sign up to set email alerts
|

Metal-insulator transition and superconductivity in boron-doped diamond

Abstract: We report on a detailed analysis of the transport properties and superconducting critical temperatures of boron-doped diamond films grown along the ͕100͖ direction. The system presents a metal-insulator transition ͑MIT͒ for a boron concentration ͑n B ͒ on the order of n c ϳ 4.5ϫ 10 20 cm −3 , in excellent agreement with numerical calculations. The temperature dependence of the conductivity and Hall effect can be well described by variable range hopping for n B Ͻ n c with a characteristic hopping temperature T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
153
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(165 citation statements)
references
References 54 publications
8
153
1
2
Order By: Relevance
“…Typical values of 10 6 K and crossovers from the VRH to the ES regime and then to a mZ1 variation at even lower temperature have been reported for type IIb single crystals with n B Z2!10 19 cm K3 (Sato et al 2000). Closer to the transition, x loc is expected to increase, leading to lower T 0 values, so that the VRH regime extends to lower temperatures, as is the case in figure 2 where T 0 is of the order of a few 10 3 K for n B Z2.4!10 20 cm K3 and several 10 2 K for n B Z4!10 20 cm K3 with a VRH regime extending down to 10 K (Klein et al 2007). Above the critical concentration, the normal-state conductivity can be extrapolated to a finite value s 0 as T/0 K, as deduced from the resistivity variations shown in figure 2.…”
Section: Doping-induced Metal-to-insulator Transitionmentioning
confidence: 94%
See 2 more Smart Citations
“…Typical values of 10 6 K and crossovers from the VRH to the ES regime and then to a mZ1 variation at even lower temperature have been reported for type IIb single crystals with n B Z2!10 19 cm K3 (Sato et al 2000). Closer to the transition, x loc is expected to increase, leading to lower T 0 values, so that the VRH regime extends to lower temperatures, as is the case in figure 2 where T 0 is of the order of a few 10 3 K for n B Z2.4!10 20 cm K3 and several 10 2 K for n B Z4!10 20 cm K3 with a VRH regime extending down to 10 K (Klein et al 2007). Above the critical concentration, the normal-state conductivity can be extrapolated to a finite value s 0 as T/0 K, as deduced from the resistivity variations shown in figure 2.…”
Section: Doping-induced Metal-to-insulator Transitionmentioning
confidence: 94%
“…Above the critical concentration, the normal-state conductivity can be extrapolated to a finite value s 0 as T/0 K, as deduced from the resistivity variations shown in figure 2. As a matter of fact, as shown in the insert of figure 3a, for n B greater than 6!10 20 cm K3 (Klein et al 2007), and below a certain temperature at which the inelastic mean free path becomes of the order of the elastic one, the resistivity increases slowly when the temperature is reduced. In this regime, where weak localization effects arising from electron-phonon scattering as well as other electronic correlations are expected, the experimental temperature dependence of the conductivity was found (Klein et al 2007) to follow between 3 and 30 K an expression of the type: sZs 0 CAT 1/2 CB e-ph T. Pronounced 'weak localization' effects have also been detected in heavily boron-doped polycrystalline (Winzer et al 2005) and nanocrystalline (Mareš et al 2006) diamond, while a sZs 0 CAT 1/3 variation has been observed in ion-implanted samples (Tshepe et al 1999).…”
Section: Doping-induced Metal-to-insulator Transitionmentioning
confidence: 98%
See 1 more Smart Citation
“…The sample has been grown by MPCVD in a vertical silica tube reactor as described elsewhere [17] on a (100)-oriented HPHT type Ib diamond substrate. After a 2 hour-long pure hydrogen plasma at 880°C, a thin non intentionally doped "buffer" layer was grown at 830°C first from 0.25% CH 4 in purified H 2 , and then the methane concentration was raised to 4% and B 2 H 6 (B/C = 1800 ppm) was added to the gas mixture without turning off the plasma, and a thicker (almost 4 µm) heavily boron-doped layer was grown.…”
Section: Methodsmentioning
confidence: 99%
“…Three samples were grown by microwave plasma chemical vapour deposition (MPCVD) in a vertical silica tube reactor as described elsewhere [10] on different diamond substrates. They were grown the same week with exactly identical growing conditions that correspond to optimum parameters for low doping.…”
Section: Methodsmentioning
confidence: 99%